Dense is not green: How visual density influences greenness evaluation on environmentally friendly products - Xiao, Chunqu; Wang, Haoyuan; Zhou, Yayu; Li, Qingyi (Frontiers in Psychology, 2023)
The visual design of environmentally friendly products has a strong influence on consumer decisions. The study offers a novel insight, suggesting that consumers’ perceptions of environmentally friendly products may be affected by the visual density design. Four experiments tested the effect of visual density on the perceived greenness of environmentally friendly products. Study 1 showed that perceived greenness was higher for environmentally friendly products with low visual density design. Study 2 repeatedly confirmed this impact and found that perceived production cost acted as a mediating factor. Study 3 and 4 found two boundary conditions for this effect. Study 3 showed that the effect of visual density design attenuated for consumers with weak holistic thinking. Study 4 further revealed that when emphasizing the use of environment-friendly materials, the effect of visual density design was also attenuated. The findings enrich the discussion on the visual design of green products, extend the effect of visual density on consumer attitudes, and provide practical implications for marketers to choose the appropriate appearance for environmentally friendly products.